Youth in participatory development at the community level - Cornwall, Grace-Ann Phidhelia (2008)
Presents an overview of the benefits of participatory development and its importance to social policy. Deals with youth in participatory development, the benefits to be derived and the factors that stymie the process of participation at the local level. Identifies policy implications and makes recommendations for sustaining youth participation in local development.